Female infertility from oocyte maturation arrest: assembling the genetic puzzle - Xinbao Ding; John C Schimenti (EMBO Molecular Medicine)
Abstract Assisted reproduction procedures often encounter an issue called oocyte maturation arrest (OMA), which is manifested as failed IVF/ICSI attempts using oocytes from some infertile women. In this issue of EMBO Molecular Medicine, Wang et al identify infertile women bearing novel DNA sequence variants in a gene called PABPC1L, which is essential for translation of maternal mRNAs. By conducting a series of in vitro and in vivo experiments, they demonstrated certain variants as being causal for OMA, confirming a conserved requirement for PABPC1L in human oocyte maturation. This study offers a promising therapeutic target for treating OMA patients.